A Study on The Msmes Growth of Teh Es Meriah and Young Seafood at Polbeng Business Expo Chapter II - Scindy Putri Febrianti Awia Citra; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting sustainable local economic growth, creating jobs, and improving community welfare. This study aims to analyze the development of MSMEs through the strategic integration of digital marketing and structured financial management, focusing on the specific case studies of Teh Es Meriah and Young Seafood during the POLBENG Business Expo Chapter II. This project was conducted at the State Polytechnic of Bengkalis in May 2025 using a practical, project-based learning approach to successfully bridge academic theory with real-world business challenges.The key project activities included producing engaging business profile videos, creating targeted digital marketing content, designing professional product catalogs, implementing QRIS as a modern digital payment system, and preparing systematic bookkeeping and financial reports before and during the intensive expo event. The research team gathered reliable primary data through direct field observation, documentation, and real-time financial transaction records.The results demonstrate that digital marketing strategies, supported by highly attractive promotional media, significantly increased consumer interest, target market reach, brand awareness, and overall sales performance. Furthermore, the implementation of QRIS greatly improved transaction efficiency, reduced human error, and enhanced financial recording accuracy. Ultimately, this comprehensive integration of digital marketing and disciplined financial management provides a scalable, highly effective model that positively contributes to sustainable MSME growth, operational independence, and competitiveness in today's rapidly evolving digital economy.